INTEGRASI ILMU PADA PROGRAM STUDI MANAJEMEN PERBANKAN SYARIAH DAN PENGARUHNYA TERHADAP KOMPETENSI LULUSAN - Hidayat, Nur (Universitas Muhammadiyah Prof DR HAMKA, 2018)
Scientific integration in higher education has an effect on graduate competency. Therefore universities must be able to develop the competencies of the students, so the students are able to have competitiveness at the national, regional and global levels. This article strengthens the concept of science integration initiated by Muslim intellectuals such as Seyyed Hossein Nasr, Syed Naquib Al-Attas, about, Rozi Al-Faruqi, Islamization of Knowledge: General Principles and Workplan. Kuntowijoyo, Science: Epistemology, Methodology, and Ethics. Maskuri Abdillah, scientific integration and its implementation in study and learning. M. Atho Mudzhar, Scientific Integration, Integration of Islamic Sciences and General Sciences. Mulyadi Kartanegara Islamization of Science, Integration of Science in the Philosophy Perspective of Science: A Holistic Reconstruction. Masri Elmahsyar Bidin, Integration of Religious and General Sciences: Finding the Format of Islamization of Science. Norazmi Anas, the Integration of Knowledge in Islam: Concept and Challenges, Universiti Sultan Zainal Abidin. Mohamed Aslam Haneef, et.al, The Effectiveness of the Integrated Curriculum: The Case of the International Islamic University of Malaysia. Rosnani Hashim, the research title is Higher Education Curriculum Development for Islamization of Knowledge. Mustafa Omar Mohammed, Integrating Al-Turath al-Islam to Modern University Curriculum: Issues and the Need for a Benchmark. Nurlena Rifa'i, Integration of Science in the Preparation and Development of Curriculum at Indonesian State Islamic Universities. Suwendi, Islamization of Science: Study of the Concepts and Practices of Education Syed Muhammad Naquib Al-Attas. Edwin Syarif, Islamization of Science at Syarif Hidayatullah State Islamic University Jakarta. The method of this research uses evaluative methods, namely the type of research that aims to evaluate and look for answers about achieving goals that have been determined and outlined previously. In this context, the use of evaluative methods is intended to evaluate the implementation of the integration of knowledge applied to the Sharia Banking Management study program. Data was also explored through documentation and observation studies. Data analysis using data collection techniques carried out through search collects and analyzes primary and secondary data sources. The integration of knowledge in the Sharia Banking Management study program influences the competency of graduates produced, the graduates produced not only have the competence (soft skills) of the theoretical concepts of Islamic banking but also understand the operations of Islamic banking (hard skills) work. Keywords: Scientific Integration, Competencies